Taxonomy and molecular phylogeny of Halymenia species (Halymeniaceae, Rhodophyta) from Southeast Asia / Tan Pui Ling - Tan, Pui Ling (2017)
Halymenia is a red algal genus classified in the family Halymeniaceae of which many of the species are poorly known. Despite the abundance of Halymenia species in the tropical and subtropical waters, there are very few studies from Southeast Asia. Traditionally, the identification of Halymenia is largely based on morphological observation in particular the vegetative features. However, these features are not sufficiently distinctive and may overlap with other taxa due to convergent evolution. The lack of distinct morphological characters has led to a need for molecular approach to address the taxonomic confusion in these red algae. Hence, both molecular analyses and morphological examination were undertaken on specimen from Malaysia, Thailand, Indonesia and the Philippines to enhance our understanding of the taxonomy and phylogeny of Halymenia in Southeast Asia. The rbcL, COI-5P, UPA and LSU (28S rDNA) markers were used to resolve the taxonomic position of Halymenia species. Combination of the following main diagnostic vegetative characters is crucial for species identification: habit, branching pattern, order of branching, presence or absence of surface proliferations or spines, blade margins, blade thickness, cortex thickness, shape and size of outer cortical cells, shape and size of inner cortical cells and presence or absence of a stipe. The molecular analyses showed that the genus Halymenia is polyphyletic and seven distinct species of Halymenia were present in our collections. Among the seven Halymenia, four were previously described (H. durvillei, H. tondoana, H. cf. dilatata, H. maculata), two were new species described from the current study (H. malaysiana, H. johorensis) and one putative new species to be described (Halymenia sp. A). Phylogenetic analyses indicated that both rbcL and COI-5P are suitable markers to elucidate taxonomic position, resolve intraspecific genetic variation of Halymenia and as potential DNA barcodes for Halymenia. In contrast, both UPA and LSU (28S rDNA) are not suitable markers for molecular phylogenetics and DNA barcoding studies in Halymenia.